PENGEMBANGAN MEDIA PEMBELAJARAN “PETUAH KIMIA” (KOMIK DIGITAL MATERI IKATAN KIMIA) - Binti Mutammimah; Wirda Udaibah (Jurnal Tadris Kimiya, 2022)
The Indonesian children's literacy is still relatively low, and it has become a severe problem that the government, teachers, parents, and librarians should face. The data shows that only 10% of Indonesian children like to read a book, while most chemistry material is written in textbooks. This study aims to produce digital comics with chemical bonding material, determine comics' feasibility, and respond to readers. The research method develops the Borg and Gall model with seven stages of development without compromising the essence of the model. Meanwhile, data collection techniques are interviews, validation, and questionnaires using a Likert scale. The media and material validator has validated the product developed in this study. As a result, the media aspect has an overall score of 48 or 100%; the score belongs to the very decent criteria. The material aspect has got a score of 26 or 93% from the basic chemistry lecturers; Also, the chemistry teachers give 100%. In addition, the digital comic readers have an extensive test. Conversely, 48 respondents have been assessed with an overall score of 2753 or 90%. Hence, this percentage value relates to the very feasible category. Thus, the characteristics of this digital comic have fulfilled the material, media, language, and visual aspects; since it is included in the worthy category as an independent learning medium without replacing the role of educators.